Transformasi Pola Visual pada Kemasan Rokok Kretek Produksi PT. Nojorono Tobacco International Kudus - Kristia Lani Diana; Naomi Haswanto; Achmad Syarief (Wimba : Jurnal Komunikasi Visual, 2015)
"Kretek" has been a heritage of Indonesian culture that id inherited for over a hundred years. It serves not only as a cultural aspects, but also as an Indonesia economical boosters; it serves 83% of the Indonesia's' gross income. In the other hand, "Kretek" is also seen as a health threat, many of government regulations are created to limit its market spread by limiting its promotion. From here, the packaging of the products become the connecting link between the producers and the consumers. Content analysis method is chosen to study the aspects that affect transformation of visual patterns in packaging of kretek. In this paper, the alteration of the visual  aspects (such such color choice, illustration, logo, and layout composition) from one periods over another is shown and explained. The object on this research is the kretek packagings that is produced by PT. Nojorono Tobacco International from when it was established in the year of 1932 untill  2013. The packagings are classified into 6 periods of developments.